Distribution of ecotypes of the genus Trifolium and annual Medicago in grazing areas in southwest Spain - González F.; Martínez N.; Moreno E. (Quality in lucerne and medics for animal production, 2001)
The need for genetic material to improve the grazing lands of the dehesa has led the Research and Technology Development Service of the Regional Government in Extremadura to establish a germplasm bank for annual leguminous forage plants. This bank contains 3361 accessions of the genus Trifolium, mainly Trifolium subterraneum, and 684 of the genus Medicago, with the majority Medicago polymorpha. In order to define a model which can be adapted to every area, it was necessary to carry out an analysis of the distribution of these species, evaluating them and relating them to the soil and climatic conditions of the area under examination. The results show that, in relation to the flowering cycle, 95 per cent of the ecotypes of the genus Trifolium fall between 118 and 170 days, while 90 per cent of the ecotypes of the genus Medicago are concentrated in a shorter cycle between 118 and 140 days.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)